Context matters: the combined influence of participation and intellectual stimulation on the promotion focus-employee creativity relationship - Zhou, Q. (2015)
In this paper, we examined the interactive effects of two contexts—participation and intellectual stimulation, and promotion focus on creativity. On the basis of a multi-organization sample of 213 employees, we tested and found that although promotion focus was positively related to creativity, the relationship between promotion focus and creativity was most positive when both participation and leader intellectual stimulation were high. We discuss the way contexts in combination influence employee creativity for promotion-oriented individuals, through increasing decision latitude as well as stimulating and promoting creativity.